The Cambrian Explosion: macroevolution and biomineralization - Mark A. S. McMenamin (Academia Biology)
Recent advances in our understanding of the Cambrian evolutionary diversification event (Cambrian Explosion) show that, although eumetazoan stem taxa were present in the late Proterozoic, a tremendous burst of macroevolutionary change occurred near the beginning of the Cambrian. Explanations relying on paleoecological feedback are insufficient to explain the macroevolutionary patterns observed, particularly those associated with the near simultaneous appearance of new higher taxa. The diversity of biomineralization types among the small shelly fossils of the early Cambrian can be explained if putative ancestral scleritome-bearers (found in both Proterozoic and Cambrian strata) had, as some new data suggest, intact scleritomes that hosted individual sclerites of varying biomineral composition.